2010
DOI: 10.1002/pmic.201000126
|View full text |Cite
|
Sign up to set email alerts
|

The Asia Oceania Human Proteome Organisation Membrane Proteomics Initiative. Preparation and characterisation of the carbonate‐washed membrane standard

Abstract: The Asia Oceania Human Proteome Organisation has embarked on a Membrane Proteomics Initiative with goals of systematic comparison of strategies for analysis of membrane proteomes and discovery of membrane proteins. This multi-laboratory project is based on analysis of a subcellular fraction from mouse liver that contains endoplasmic reticulum and other organelles. Here we present the strategy used for preparation and initial characterisation of the membrane sample, including validation that the carbonate-washi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Peng’s group recommended the use of a similar method for enrichment of membranes from the liver microsomal fraction, to be followed by SDS-PAGE, tryptic digestion of excised proteins and identification by LC-MS/MS [15]. The Peng’s group protocol was also discussed by the Asia Oceania Proteome Organization Membrane Proteomics Initiative as a standard protocol for sample preparation for further proteomic analysis of membrane proteins [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Peng’s group recommended the use of a similar method for enrichment of membranes from the liver microsomal fraction, to be followed by SDS-PAGE, tryptic digestion of excised proteins and identification by LC-MS/MS [15]. The Peng’s group protocol was also discussed by the Asia Oceania Proteome Organization Membrane Proteomics Initiative as a standard protocol for sample preparation for further proteomic analysis of membrane proteins [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, SDS‐PAGE separation and in‐gel digestion were used in reference , which led to higher labor and time consumed. For number of CYPs and UGTs, our protocol generated slightly higher number of CYPs (27 versus 25) and UGTs (12 versus 9) than that in reference , and lower number of CYPs (27 versus 35) than that in reference . Considering the differences of mass spectrometer and sample preparation method used in our protocol and reference (LTQ versus LTQ‐Orbitrap, in‐solution digestion versus SDS‐PAGE separation and in‐gel digestion) and also the difference of analyzed sample (human liver microsome versus mouse liver microsome), the results indicate that our protocol is valuable for comprehensive membrane proteome analysis of liver microsome, especially CYPs and UGTs analysis.…”
Section: Cyps and Ugts Identified With Sds‐page‐free Protocolmentioning
confidence: 89%
“…These results demonstrated that the SDS-PAGE-free protocol could obtain comprehensive and accurate information about the relative abundance of CYPs and UGTs in HLMs. We also compared the results from our protocol with that from references [29] and [30] for liver microsome membrane proteome analysis. Peng et al [29] applied sodium carbonate (pH 11.5) washing step for enrichment of integral and lipid-anchored membrane proteins from mouse liver microsome, followed by in-solution trypsin digestion and LC-ESI-MS/MS (LTQ) analysis.…”
mentioning
confidence: 99%
“…Several previously published reports have described the analysis of plasma membrane (47,49,50) and microsomal membrane proteins (49, 51, 52) of mouse or rat liver origin. Two observations are noteworthy when the current data are compared with those reported previously.…”
Section: Development Of Centrifugal Proteomicmentioning
confidence: 99%